Molecular Diagnosis of Neurofibromatosis by Multigene Panel Testing - Zhang, Zeng-Yun-Ou; Wu, Yuan-Yuan; Cai, Xin-ying; Fang, Wen-Liang; Xiao, Feng-Li (Frontiers in Genetics, 2021)
Abstract Neurofibromatosis (NF) is an autosomal genetic disorder for which early and definite clinical diagnoses are difficult. To identify the diagnosis, five affected probands with suspected NF from unrelated families were included in this study. Molecular analysis was performed using multigene panel testing and Sanger sequencing. Ultradeep sequencing was used to analyse the mutation rate in the tissues from the proband with mosaic mutations. Three different pathogenic variants of the NF1 gene were found in three probands who mainly complained of café-au-lait macules (CALMs), including one frame-shift variant c.5072_5073insTATAACTGTAACTCCTGGGTCAGGGAGTACACCAA:p.Tyr1692Ilefs in exon 37, one missense variant c.3826C>T:p.Arg1276Ter in exon 28 and one splicing variant c.4110+1G>T at the first base downstream of 3'end of exon 30. One NF1 gene mosaic variant was found in a proband who complained of cutaneous neurofibroma with the frame-shift variant c.495_498del:p.Thr165fs in exon 5, and ultradeep sequencing showed the highest mutation rate of 10.81% in cutaneous neurofibromas. A frame-shift variant, c.36_39del:p.Ser12fs in exon 1 of the NF2 gene, was found in a proband who presented with skin plaques and intracranial neurogenic tumours. All of these pathogenic variants were heterozygous, one was not reported and one not in Chinese before. This study expands the pathogenic variant spectrum of NF and demonstrates the clinical diagnosis.